M&A im Bereich Erneuerbarer Energien - Sebastian G. Fritz-Morgenthal; Sebastian T. Hach; Christoph Schalast (Frankfurt School of Finance & Management, 2010)
Several top deals already closed, a still highly fragmented industry and strong pressure for further consolidation following the financial crisis - renewable energy certainly has become a red-hot topic in M&A. Surveying 220 companies in the solar photovoltaic, utility and financial sector as well as major technology corporations, which are identified as the key industries in the sector-specific takeover market, this working paper proves the common knowledge for the example of photovoltaics. With more than 93% of the respondents, a vast majority expects the M&A environment to further ameliorate and deals to increase. As for the fundamental market drivers, the survey suggests a shift from factors linked to the financial crises towards an increasing impact of general industry-related influences. In contrast, neither the industry sector nor other corporate characteristics are of significant importance. With respect to prevailing takeover strategies, the survey reveals a strong influence of general acquisition motives. However, an empirically significant connection can be determined between the industry sector of potential buyers and the most relevant motivation factors, which allows for the assumption of business-affected takeover strategies that are elaborated on more closely within the working paper. Examining an acquisition focus in terms of the targets' position in the photovoltaic value chain, no statistically valid connection can be observed with either the acquisition motivation or the industry sector of the potential buyer, leaving room for further research.
Keywords: K12; K19; K22; K29; 330; Erneuerbare Energien; Renewable Energy; Solarenergie; Photovoltaik; M&A; Merger; Acquisition; Konsolidierung; Akquisitionsstrategie; Finanzkrise; EEG; Solarförderung; Energiewirtschaft; Versorgungssicherheit; Energieabhängigkeit; Nachhaltigkeit; Sustainability; Sonnenenergie; Photovoltaikanlage; Übernahme; Fusion; Unternehmensentwicklung; Förderung regenerativer Energien; Deutschland